Production, intake, and feeding behavior of dairy goats fed alfalfa via grazing and cassava - Marques, Raquel Ornelas [UNESP]; Gonçalves, Heraldo Cesar [UNESP]; de Lima Meirelles, Paulo Roberto [UNESP]; de Paula Ferreira, Reinaldo; Gomes, Helen Fernanda Barros; Lourençon, Raquel Vasconcelos; Brito, Evelyn Prestes [UNESP]; Cañizares, Gil Ignacio Lara (Revista Brasileira de Zootecnia, 2022)
This study examined the replacement of maize and soybean meal with cassava chips and alfalfa grazing, respectively. Twelve lactating Anglo-Nubian goats were kept on a Panicum maximum cv. Tobiatã pasture. The experiment was laid out in a Latin square design in which the following diets were tested: ground maize + soybean meal, cassava chips + soybean meal, ground maize + alfalfa grazing, and cassava chips + alfalfa grazing. The evaluated variables were feed intake, daily weight gain, milk yield and composition, and feeding behavior of the goats as well as production costs. Cassava chips and grazed alfalfa influenced the intakes of dry matter, crude protein, neutral detergent fiber, and total digestible nutrients. However, milk yield, body weight, and body score did not change. There was no diet effect on the proportions of protein, solids-not-fat, somatic cell count, or urea nitrogen in the milk. Treatments influenced the levels of fat, lactose, and total solids in milk, with the highest fat levels achieved with diets containing alfalfa. Grazing, rumination, and idle times and time spent interacting with other goats were not influenced by diets. The evaluated feedstuffs improved feed efficiency and reduced production costs. Therefore, cassava chips and alfalfa can replace certain ingredients without impairing the production performance of goats, but rather improving the profit of the producer.
Keywords: Goat; Grass; Milk composition; Pasture